Espiritualidade e saúde mental: exploração de relações curvilineares a partir de uma nova escala de crenças espirituais - Daniel Foschetti Gontijo (2019)
Gathered evidence increasingly show that, the higher the levels of someone’s religiosity/spirituality (R/S), the better tends to be his/her mental health. However, relatively few studies include significant proportions of non-religious/spiritualized people in their sample, and some findings suggest that the relation between these two variables are not linear, but rather curvilinear. This might imply that, in comparison to people who show intermediate levels of R/S, those who show higher levels and those who show lower levels tend to be mentally healthier. So far, this “curvilinear model” was rarely tested, and no study has done it through a measure of beliefs in spiritual beings – the main characteristic of spirituality. In light of that, in Study 1, we develop and test the validity of the Beliefs in Spiritual Beings Scale (BSBS). Through an online platform, 1788 Brazilians of different religious/spiritual denominations answered ECSE and five theoretical related measurements, and preliminary evidence for its validity were found. In Study 2, this same sample was assessed for positive (i.e., happiness, and meaning in life) and negative (i.e., symptoms of anxiety, and symptoms of depression) components of mental health. Results of regression analysis showed curvilinear relations between R/S – as assessed by ECSE and by a religiosity scale – as well as the aforementioned components. However, when considering the predictive power of religiosity, level of belief in spiritual beings only predicted variance in meaning in life. Curvilinear relationships were more evident in models involving symptoms of anxiety and depression. Complementary analysis showed that, in comparison to groups showing intermediate levels of R/S (i.e., that of nonreligious spiritualists and those of agnostic non-spiritualists), the group showing the highest level (i.e., that of religious spiritualists) and the group showing the lowest level (i.e. that of gnostic non-spiritualists) were composed of more mentally healthy people. Although religious spiritualists and gnostic non-spiritualists had similar levels of symptoms of anxiety and depression, the former presented more happiness and meaning in life. Taken together, these findings corroborate the curvilinear model, but suggest that R/S relates in different ways to the positive and negative components of mental health.